Improving the Durability of Pozzolan Concrete Using Alkaline Solution and Geopolymer Coating. (2015) - Wiyono, David; Antoni,; Hardjito, Djwantoro
Abstract: Durability is a major concern for concrete, therefore initiatives are needed to improve the durability of concrete. One way to improve concrete durability is improving its surface quality. This study focuses on the improvement of the surface durability of pozzolan concrete by applying coating of alkali solution or geopolymer paste. There were two different pozzolanic materials used to manufacture the pozzolan concrete, i.e. class-F fly ash and calcined volcanic mud with two different particle sizes. The alkaline solution was a combination of NaOH and sodium silicate solution. Fly ash-based geopolymer paste was prepared for the geopolymer coating. Concrete specimens were exposed to 10% sulphuric acid solution by applying the wet–dry cycles to accelerate the damage process, and to chloride solution to evaluate its penetration depth. The results show that applying the alkaline solution and geopolymer coating improves the durability of pozzolan concrete.